2014
DOI: 10.1242/jeb.110601
|View full text |Cite
|
Sign up to set email alerts
|

The amphibious fishKryptolebias marmoratususes alternate strategies to maintain oxygen delivery during aquatic hypoxia and air exposure

Abstract: Despite the abundance of oxygen in atmospheric air relative to water, the initial loss of respiratory surface area and accumulation of carbon dioxide in the blood of amphibious fishes during emersion may result in hypoxemia. Given that the ability to respond to low oxygen conditions predates the vertebrate invasion of land, we hypothesized that amphibious fishes maintain O 2 uptake and transport while emersed by mounting a co-opted hypoxia response. We acclimated the amphibious fish Kryptolebias marmoratus, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 79 publications
2
44
2
Order By: Relevance
“…Gracey, 2008). However, we have found that this is not the case in K. marmoratus (Turko et al, 2014). Here, terrestrial acclimation results in a significant increase in the affinity of Hb for O 2 , which is not observed in hypoxiaacclimated K. marmoratus in water.…”
Section: Gas Exchange and Metabolismcontrasting
confidence: 57%
See 1 more Smart Citation
“…Gracey, 2008). However, we have found that this is not the case in K. marmoratus (Turko et al, 2014). Here, terrestrial acclimation results in a significant increase in the affinity of Hb for O 2 , which is not observed in hypoxiaacclimated K. marmoratus in water.…”
Section: Gas Exchange and Metabolismcontrasting
confidence: 57%
“…To increase blood flow and facilitate O 2 transfer across respiratory surfaces, including the cutaneous surface, there are rapid circulatory adjustments (Table 3). It is not clear in various amphibious fishes whether these gas exchange organs are primed and ready for aerial respiration, such as in the mudskipper P. schlosseri (Gonzales et al, 2011), or whether angiogenesis occurs in these extrabranchial respiratory surfaces as they acclimate to air exposure, as in the mangrove rivulus K. marmoratus; here, there is evidence of angiogenesis in the bucco-opercular lining, skin and fins after 7 days out of water relative to control fish in water Turko et al, 2014).…”
Section: Gas Exchange and Metabolismmentioning
confidence: 89%
“…Most fishes possess mechanisms that enhance O 2 extraction and delivery to tissues as Pw O2 is reduced, such as increased haemoglobin (Hb) synthesis (Gracey et al, 2001) and concentration in the blood (Affonso et al, 2002), increased haematocrit (Lai et al, 2006;Turko et al, 2014), increased Hb-O 2 binding affinity (Turko et al, 2014), increased ventilation frequency and amplitude (Holeton and Randall, 1967;Itazawa and Takeda, 1978;Tzaneva et al, 2011;Vulesevic and Perry, 2006), and a redistribution of blood supply to critical tissues (Sundin et al, 1995). Some fishes, including goldfish and numerous other species, also have the ability to dramatically increase lamellar surface area in response to hypoxia exposure through apoptotic reductions to the inter-lamellar cell mass (ILCM; Anttila et al, 2015;Borowiec et al, 2015;Crispo and Chapman, 2010;Dhillon et al, 2013;Ong et al, 2007;Sollid et al, 2003Sollid et al, , 2005Turko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Can short-term acclimation to terrestrial environments also cause reversible plasticity in skeletal muscle and locomotory performance in amphibious fishes? The amphibious mangrove rivulus Kryptolebias marmoratus reversibly remodels respiratory surfaces and blood O 2 transport after a week out of water remaining relatively quiescent (Ong et al, 2007;Turko et al, 2014); however, it is unknown whether locomotory performance is also altered.…”
Section: Introductionmentioning
confidence: 99%